Heating technology for malignant tumors: a review. (1st January 2020) - Kok, H. Petra; Cressman, Erik N. K.; Ceelen, Wim; Brace, Christopher L.; Ivkov, Robert; Grüll, Holger; ter Haar, Gail; Wust, Peter; Crezee, Johannes
Abstract: The therapeutic application of heat is very effective in cancer treatment. Both hyperthermia, i.e., heating to 39–45 °C to induce sensitization to radiotherapy and chemotherapy, and thermal ablation, where temperatures beyond 50 °C destroy tumor cells directly are frequently applied in the clinic. Achievement of an effective treatment requires high quality heating equipment, precise thermal dosimetry, and adequate quality assurance. Several types of devices, antennas and heating or power delivery systems have been proposed and developed in recent decades. These vary considerably in technique, heating depth, ability to focus, and in the size of the heating focus. Clinically used heating techniques involve electromagnetic and ultrasonic heating, hyperthermic perfusion and conductive heating. Depending on clinical objectives and available technology, thermal therapies can be subdivided into three broad categories: local, locoregional, or whole body heating. Clinically used local heating techniques include interstitial hyperthermia and ablation, high intensity focused ultrasound (HIFU), scanned focused ultrasound (SFUS), electroporation, nanoparticle heating, intraluminal heating and superficial heating. Locoregional heating techniques include phased array systems, capacitive systems and isolated perfusion. Whole body techniques focus on prevention of heat loss supplemented with energy deposition in the body, e.g., by infrared radiation. This review presents an overview of clinical hyperthermia and ablation devices used for local, locoregional, and whole body therapy. Proven and experimental clinical applications of thermal ablation and hyperthermia are listed. Methods for temperature measurement and the role of treatment planning to control treatments are discussed briefly, as well as future perspectives for heating technology for the treatment of tumors. Graphical Abstract: Schematic overview of clinically proven heating techniques used for various indications and tumor locations.